PENERAPAN MIND MAPPING DALAM UPAYA PENINGKATAN KETERAMPILAN PROSES SAINS MAHASISWA PADA MATAKULIAH MIKROBIOLOGI MELALUI LESSON STUDY - Muh. Waskito Ardhi (Florea : Jurnal Biologi dan Pembelajarannya, 2014)
Lesson study is a model of professional development of educators through collaborative research and continuous learning based on the principles of mutual kolegalitas and learning to build community study. Lesson study can be implemented at various levels of education , including college. The level of implementation of the Lesson study done is learning plan, implementation of learning, and reflection. Lesson study cycle is done 4 times with the topic Fungi, Sterilization, Media Bacteria and Isolation, and Environmental Microbiology. Lesson study results showed an increase in the quality of learning that is Microbiology Subjects with variations learning methods , learning strategies, media variations, and how to evaluate, especially in the use of Mind Mapping . Lesson study is ongoing implementation will accelerate the implementation of professional development learning. Increased professionalism of lecturers will be followed by an increase effectiveness of learning and teaching and will indirectly have an impact on improving the quality of education at large.